THE FORMULATION OF DRY CURCUMA (CURCUMA XANTHORRHIZA ROXB.) EXTRACT MICROCAPSULES BY SPRAY WET MICROENCAPSULATION TECHNIQUES - Samran, Samran; Dalimunthe, Dalimunthe; Dalimunthe, Dalimunthe; Dalimunthe, Dalimunthe (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Curcuma xanthorrhiza Roxb. was used as hereditary medicinal plant for prevention of liver dysfunction, gastrointestinal disease, fever, and hemorrhoid. Curcuma extract was easy to damage because the light exposure, change of pH, weather and a long period of storage time. The problem can be solved by coating the extract with spray wet microencapsulation (SWM) technique. SWM technique is a method of preparing microcapsules in which a solution, suspension, or emulsion with a charged matrix is sprayed into opposing solution. The aim of this research was to formulate the dry Curcuma extract with SWM technique using sodium alginate as matrix. Methods: Brown algae (Sargassum ilicifolium) was a main resource of alginate acid. It was isolated using HCl 5% to make alginate acid and sodium alginate that was obtained by adding Na2CO3 5% to alginate acid solution. The microencapsulation process of Curcuma extract was done by SWM technique. The formula of Curcuma extract microencapsulation was design into three formulas: F1, F2, and F3. Microcapsules of Curcuma extract were being characterized for color intensity, analysis of scanning electron microscope (SEM), compressibility index, flowing time, and determination of angle repose. Results: The results showed that the higher concentration of sodium alginate used, the dry Curcuma extract microcapsules produced better. Particle size of extract microcapsules of Curcuma extract microcapsules SEM from F1, F2, F3 was 20 Î¼m whereas dry weight of extracted microcapsule of Curcuma grows with increasing concentration of sodium alginate: F1 (0.2%) 19.86Â±0.11 g, F2 (0.4%) 20.66Â±0.73, F3 (0.6%) 21.29Â±0.64. The flowing time of F1, F2, and F3 was 6.92Â±0.56, 7.42Â±0.50, and 8.05Â±0.54 s consecutively. Conclusions: Based on the analysis of the study result, it can be concluded that the raw materials of Curcuma extract can be made by SWM technique using sodium alginate isolated from brown algae, and the characterization of dry Curcuma extract microcapsule of the three formulas met the requirements of the pre-formulation tests for capsule dosage form.